PAIN IN THE LOWER BACK: A DIFFERENTIATED THERAPY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Pain in the lower back is one of the most frequent reasons for patients to see a doctor. 30-60% of the population in developed countries suffers from recurrent back pain, and up to 80% of all back pain occurs in the lumbar region of the back. All age groups can suffer from lumbar pain, but the peak incidence occurs at the age of 30 to 60 years. This is largely due to the aging processes of inter vertebral discs (macroscopic changes in the fibrous ring and the pulpous nucleus). However, the degenerative process in the spine itself can only be considered a prerequisite for pain in the lower back, but not the direct cause. Sources of pain impulses in vertebral pain can be not only altered inter vertebral discs, but also spinal ligaments, periosteal joint tissue and periarticular tissue, spasmodic muscles surrounding the affected vertebral motor segment.